t+3t-7=4+-7

Simple and best practice solution for t+3t-7=4+-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t+3t-7=4+-7 equation:


Simplifying
t + 3t + -7 = 4 + -7

Reorder the terms:
-7 + t + 3t = 4 + -7

Combine like terms: t + 3t = 4t
-7 + 4t = 4 + -7

Combine like terms: 4 + -7 = -3
-7 + 4t = -3

Solving
-7 + 4t = -3

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 4t = -3 + 7

Combine like terms: -7 + 7 = 0
0 + 4t = -3 + 7
4t = -3 + 7

Combine like terms: -3 + 7 = 4
4t = 4

Divide each side by '4'.
t = 1

Simplifying
t = 1

See similar equations:

| 70x+40=6 | | -100+4s=50 | | 4/2x-5/2x+9/2x | | 10-5+3x+2x=0 | | 5x-28=3x+10 | | (2x^2+4x)+(3x^2+2x)= | | 4/2x | | 1+2+3=24 | | 2+4w=-26 | | (8x+5)+(19-8x)= | | 67x+13=6 | | 7+2+8=216 | | -5+9d=49 | | -17+3x=-41 | | 8/3*10 | | g^3+3g^2-y-3=0 | | 0=2+2Q+2Q^2 | | 2y=1.5x-8 | | 4v^5(v^2-4v+14)= | | 11-9m=70 | | (7/6n-84n+288)-5/5n^2-40n | | -x/4-2=-10 | | 336+25p=550 | | 2m^3n^3/3m^-4n^3x3m^4n-1 | | 6x+14=38 | | 4x^2-3x^2= | | 18s^2-50s=0 | | -36=j+13forj | | x+2x+2x-1=24 | | 4v^7-16v^6+56v^5= | | 2x+3y+5z=90 | | 16*3/5 |

Equations solver categories